The Effect of Profitability, Firm Growth, and Firm Size to The Capital Structure of Manufacturing Firms in Indonesia Stock Exchange in 2017-2018 - Septy Dwi Indah Sari; Ati Sumiati; Sri Zulaihati (Jurnal Akuntansi, Perpajakan dan Auditing, 2020)
The research aims to know an affection between profitability, firm growth, and firm size to the capital structure of manufacturing firms in the Indonesia Stock Exchange in 2017-2018. The method used of research is quantitative method with secondary data obtained from the company's annual report with 78 samples. The data analysis technique uses the requirements analysis test, classic assumption test, multiple regression equation test, and hypothesis test. The research results partially show that profitability and company size have positive and significant effects on capital structure; company growth has a negative and significant effect on capital structure; and simultaneously affect the capital structure.